Product variety, price elasticity of demand and fixed cost in spatial models - Yiquan Gu; Tobias Wenzel (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institut für Wirtschaftspolitik und Quantitative Wirtschaftsforschung (IWQW), 2009)
This paper explores the implications of price-dependent demand in spatial models of product differentiation. We introduce consumers with a quasi-linear utility function in the framework of the Salop (1979) model. We show that the so-called excess entry theorem relies critically on the assumption of completely inelastic demand. Our model is able to produce excessive, insufficient, or optimal product variety. A proof for the existence and uniqueness of symmetric equilibrium when price elasticity of demand is increasing in price is also provided.
Keywords: L11; L13; 330; Demand elasticity; Spatial models; Excess entry theorem; Produktdifferenzierung; Monopolistischer Wettbewerb; Preiselastizität; Fixkosten; Hotelling Modell; Theorie